«Моральна сліпота» зігмунда баумана та етика відповідальності у філософському дискурсі - Олійник Вікторія; Oliinyk Viktoriia (Видавництво «Код», 2025)
Резюме. У статті досліджується феномен моральної сліпоти в інтерпретації Зігмунта Баумана та його взаємозв’язок із концепцією етики відповідальності. Проаналізовано соціальні механізми формування моральної байдужості в сучасних суспільствах та запропоновано шляхи подолання цього явища через відповідальну етичну позицію. Здійснено ретроспективний аналіз етики європейської гуманістичної традиції. Досліджено, що питання формування соціальних цінностей. протистояння моральній релевантності – були центральним у європейській філософії.

Abstract. The article explores the phenomenon of moral blindness in the interpretation of Zygmunt Bauman and its relationship with the concept of ethics of responsibility. The social mechanisms of the formation of moral indifference in modern societies are analyzed and ways of overcoming this phenomenon through a responsible ethical position are proposed. A retrospective analysis of the values of the humanistic tradition shows that the issues of the formation of social values - opposition to moral relevance – were central in European philosophy. Modern research integrates Bauman’s ideas and proposes an ethics of responsibility as the opposite of moral petrification. However, a comprehensive analysis that directly contrasts the mechanisms of «moral blindness» with the constructive principles of the ethics of responsibility as a practical strategy of resistance remains insufficiently developed. The issue of moral blindness as existential indifference and ethics of responsibility is reflected in the works of many modern scholars. Bauman’s concept, set out in the work «Modernity and the Holocaust», has become the subject of critical analysis and development. Bauman considers the Holocaust not as an atavism of barbarism, but as a product of modern rational civilization. The key concept here is «moral blindness» a state when technological, bureaucratic and social mechanisms systematically suppress the moral state of a person. The main sign of this is a social distance, which is revealed through the flourishing of bureaucracy and the distribution of labor. Researchers develop the Bauman’s thoughts and focus on the technological aspects of moral degradation in the era of digitalization. It is now that social media and algorithms are creating new forms of distancing and dehumanization. The purpose of this article is a systematic analysis of the phenomenon of «moral blindness» in the philosophical interpretation of Zygmunt Bauman and an investigation of the potential of the ethics of responsibility as a philosophical and practical alternative for overcoming this phenomenon in the conditions of modern society.
Zigmund Bauman’s «Moral blindness» and the ethics of responsibility in philosophical discourse
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-17?authuser=0
Keywords: втрата чутливості; банальність зла; моральна сліпота; етика відповідальності; колективна відповідальність; цінності